An Empirical Analysis of Demand Determinants for Women’s Apparel in Emerging Markets - Ashan, Muhammad; Khan, Verdah; Nizami, Umair (Journal of Development and Social Sciences, 2025)
With an eye toward economic, psychological, and cultural impacts especially in Karachi, this study seeks to pinpoint and examine main elements driving demand in Pakistan’s women’s apparel sector. Although the women’s clothing market of Pakistan is growing, it is still difficult to forecast because of changing customer behavior impacted by cultural changes, economic variance, and changing digital trends. Strategic decisions and inventory control suffer inaccurate demand predictions. Survey data gathered from Karachi female consumers was a quantitative one. Examined in relation to income levels, brand loyalty, price sensitivity, and product preferences was regression analysis. Results show that main economic drivers are pricing policy and discretionary income. Purchasing behavior is greatly shaped by cultural inclination for simple and classic designs as well as by digital marketing and social media. High expenses prevent the acceptance of sustainable fashion even if environmental awareness is growing. Advice for clothing companies should be to use flexible pricing policies, stress distinctive brand identities, and improve online interaction. In the garment business, knowledge of demand elements helps to improve forecasting, competitiveness, and sustainable development.